Effect Of Motivation, Wages, Labor And Social Security Personnel On The Performance Of Hygiene District Department Of Environmental Nganjuk - Nandhi Roro Gesang; Supriyono Supriyono (Universitas Islam Kadiri, 2020)
This study aimed to determine the effect of motivation variables, Wages, Labor and Social Security on the performance of a janitor, both simultaneously and partially on the performance of a janitor. The variables in this study consisted of independent variables in the form of motivation which consists of physiological needs, safety needs, social needs, the needs of self-esteem and self-actualization needs. Variable salary consists minimum wage, overtime, wages do not work due to other activities outside of work, and the structure and scale of remuneration proportional. Social security workforce composed of Accident Insurance (JKK), Death Benefit (JKM), the Old Age Security JHT) and pensions (JP). The dependent variable in the form of Performance Officer Hygiene. Performance consists of quantity, quality, punctuality, attendance, and ability to cooperate. This research is a quantitative research, with a population of 135 people janitor. The sampling technique was conducted using purposive sampling, with a sample of 100 people. The test results of T-test, partial variabel motivation significant effect of 0,388 to variable performance janitor Environment Agency Nganjuk. In partial wage, significant influence amounted to 0.865 against the performance variables janitor Environment Agency Nganjuk. In partial social securityberpengaruh significantly by 0.207 to variable performance janitor District Environmental Office. Nganjuk. F test results - Test Variables Motivation, Wages, Labor and Social Security amounted to 141.596 simultaneous effect on the performance of the janitor of the Environment Department Nganjukreinforced by the coefficient of determination coefficient of determination (R) = 0816 means the relationship between motivation, wages and social security to the performance janitor of 81.6% means a very close relationship. The greater the R means the relationship more closely. While the R square of 0.810 means that 81% can be explained by the motivation variable (X1), wages (X2) and social security of labor (X3) and performance (X4). While the remaining 19% can be explained by other factors not examined in this study.